2001
DOI: 10.1074/jbc.m107798200
|View full text |Cite
|
Sign up to set email alerts
|

Solution Conformation of α-Conotoxin EI, a Neuromuscular Toxin Specific for the α1/δ Subunit Interface of Torpedo Nicotinic Acetylcholine Receptor

Abstract: A high resolution structure of ␣-conotoxin EI has been determined by 1 H NMR spectroscopy and molecular modeling. ␣-Conotoxin EI has the same disulfide framework as ␣4/7 conotoxins targeting neuronal nicotinic acetylcholine receptors but antagonizes the neuromuscular receptor as do the ␣3/5 and ␣A conotoxins. The unique binding preference of ␣-conotoxin EI to the ␣ 1 /␦ subunit interface of Torpedo neuromuscular receptor makes it a valuable structural template for superposition of various ␣-conotoxins possessi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 61 publications
2
30
0
Order By: Relevance
“…Despite their differences in primary sequence, NMR and X-ray crystallography studies show a high conservation of the structural peptide backbone (Hu et al, 1996(Hu et al, , 1997(Hu et al, , 1998Shon et al, 1997;Hill et al, 1998;Cho et al, 2000;Park et al, 2001;Nicke et al, 2003). It seems that this backbone serves as a scaffold that presents a variety of amino acid side chains leading to differences in specificity.…”
Section: Discussionmentioning
confidence: 99%
“…Despite their differences in primary sequence, NMR and X-ray crystallography studies show a high conservation of the structural peptide backbone (Hu et al, 1996(Hu et al, , 1997(Hu et al, , 1998Shon et al, 1997;Hill et al, 1998;Cho et al, 2000;Park et al, 2001;Nicke et al, 2003). It seems that this backbone serves as a scaffold that presents a variety of amino acid side chains leading to differences in specificity.…”
Section: Discussionmentioning
confidence: 99%
“…Ligand binding modes of these residues have been confirmed in recent homology modeled structures of nAChRs (31) and the x-ray structures of AChBP bound to α-conotoxins (23,25,32) or α-cobratoxin (33). Another strategy for studying nAChR-ligand interactions has been to identify potential receptor-binding pharmacophores within various ligands including α-conotoxins (16,17,19,21,(34)(35)(36)(37). Here, we have generated high-resolution structures of ligand-nAChR complexes using α-conotoxin GIC, a well-known antagonistic ligand of nAChRs, and the extracellular domains of nAChRs that are homology modeled using the α1 subunit of mouse, which has much higher sequence homology with nAChR subunits than acetylcholine binding protein (AChBP).…”
Section: Resultsmentioning
confidence: 99%
“…Extensive structural characterization and comparison of several α-conotoxins suggested residues that might be important for their subtype recognition specificities Table 1 (14)(15)(16)(17)(18)(19)(20). In particular, the structural studies on the α4/7-conotoxins have shown that these toxins with a same "ω-shaped" backbone topology can display a widely different receptor recognition profiles by relying on subtle differences in their surface properties (14,15,19,21). Above all, the precise delineation of contact sites that are responsible for specific recognition between a particular receptor subtype and its ligands requires high-resolution structures of the complexes of many receptor subtypes with various ligands displaying a large window of affinities.…”
Section: Introductionmentioning
confidence: 99%
“…obtain such information have not been successful (36 -38) even though a low resolution electromagnetic image (39,40) and an x-ray structure of an acetylcholine-binding protein that resembles the extracellular domain of nAChR have been obtained (41). In the absence of a high resolution structure of nAChR, we have been determining high resolution structures of ␣/␣A-conotoxins and tried to "reverse-predict" the receptor residues that might interact with the receptor-contacting residues of ligands (12)(13)(14)(15). Such an approach is possible because although various ␣/␣A-conotoxins exhibit a great variety of receptor subtype specificity, they differ only slightly in their sequences with a similar overall fold exhibiting subtle local structural differences.…”
Section: Discussionmentioning
confidence: 99%
“…In an effort to discover novel modulators of nAChR by identifying critical residues within the toxin for receptor contact, we have been applying a "reverse mapping strategy" using atomic resolution structures of various ␣/␣A-conotoxins (12)(13)(14)(15). Although considerable structure-function work has been reported on the ␣-conotoxins (16 -25), there has been only one report on the ␣A-subfamily (12) since their original discovery (6).…”
mentioning
confidence: 99%